IMPROVING NARRATIVE TEXT WRITING SKILLS USING PROJECT-BASED LEARNING TECHNIQUES IN ELEMENTARY SCHOOL - Markus Harefa; Nidya Chandra Muji Utami; Fahrurrozi (Universitas Majalengka, 2023)
Writing narrative text is one of the important aspects of language education that involves students' ability to organize their ideas into a coherent and meaningful narrative. However, many students face difficulties in writing narrative texts due to lack of practical experience and lack of imaginative stimulation. In this regard, the Project Based Learning (PjBL) technique has proven to be an effective teaching approach in developing students' writing skills and imaginative abilities. PjBL engages students in real projects or tasks that require problem solving, research and collaboration. In the context of writing narrative texts, PjBL allows students to develop their writing skills through projects that encourage imagination, creativity, and collaboration. This study aims to see how the Project Based Learning (PjBL) technique can improve narrative text writing skills while developing imaginative ideas and self-confidence of fifth-grade students of SDN Semplak 2 Bogor. This study used classroom action research with 2 cycles following the Kemmis and Taggart model. Each cycle includes 4 stages: planning, implementation, observation, and reflection. The subjects of this study involved 17 fifth-grade students. Data were obtained using tests and words. The findings of this study indicate that the Project Based Learning (PjBL) technique can help improve narrative text writing skills. The results showed an increase in Project Based Learning (PjBL) writing skills in fifth-grade students. Menulis teks naratif adalah salah satu aspek penting dalam pendidikan bahasa yang melibatkan kemampuan siswa untuk mengorganisir ide-ide mereka menjadi sebuah narasi yang koheren dan bermakna. Namun, banyak siswa menghadapi kesulitan dalam menulis teks naratif karena kurangnya pengalaman praktis dan kurangnya rangsangan imajinatif. Dalam hal ini, teknik Project Based Learning (PjBL) telah terbukti menjadi pendekatan pengajaran yang efektif dalam mengembangkan kemampuan menulis dan kemampuan imajinatif siswa. PjBL melibatkan siswa dalam proyek atau tugas nyata yang membutuhkan pemecahan masalah, penelitian, dan kolaborasi. Dalam konteks menulis teks naratif, PjBL memungkinkan siswa untuk mengembangkan kemampuan menulis mereka melalui proyek yang mendorong imajinasi, kreativitas, dan kolaborasi. Penelitian ini bertujuan untuk melihat bagaimana teknik Project Based Learning (PjBL) dapat meningkatkan keterampilan menulis teks naratif sekaligus mengembangkan ide imajinatif dan kepercayaan diri siswa kelas V SDN Semplak 2 Bogor. Penelitian ini menggunakan penelitian tindakan kelas dengan 2 siklus yang mengikuti model Kemmis dan Taggart. Setiap siklus meliputi 4 tahap yaitu perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian ini melibatkan 17 siswa kelas V. Data diperoleh dengan menggunakan tes dan kata-kata. Temuan dari penelitian ini menunjukkan bahwa teknik Project Based Learning (PjBL) dapat membantu meningkatkan keterampilan menulis teks naratif. Hasil penelitian menunjukkan adanya peningkatan keterampilan menulis teks naratif melalui Project Based Learning (PjBL) pada siswa kelas V SD.